An Analysis of the Relation Between Parental Practices and Preschoolers Self-concept. (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
This study aimed to relate parental practices to the establishment of self-concept in preschoolers. Participants were 55 children from both genders, registered in Curitiba city public schools, and their parents. It was used the correlation method of study, in which children had their self concept evaluated by a previously selected measurement tool. The parental practices were assessed by observing two game situations with the family triad, video and audio recorded. Categories related to the parental practices were developed in order to have them observed and counted by two blind judges. The categories were: Positive Instruction of Verbal Interaction (IP), Coercive Instruction of Verbal Interaction (IC), Simple Verbal Interaction (VS), Positive Verbal Interaction (VP), Coercive Verbal Interaction (VC), Positive Non-verbal Interaction (NVP), Coercive Non-verbal interaction (NVA), Doing for the child (FP). Through statistic analysis was found that children with a positive self-concept have parents that provide more positive reinforced behaviors. Children with a negative self-concept have more coercive parents, in other words, parents that teach more by rule controlled behaviors, making hard to their kids learn how to discriminate contingencies. In this sample the boys´ self-concept was better established than those of girls of the same age. Children with intact families had also a higher self-concept. To Behavior Analysis the self-concept is acquired in the relationship with others. It is in the interaction with the external environment that the children learn to discriminate their inner stimuli, and thus built the self-concept based on the experiences mediated by the verbal community.
Keywords: Self-concept; parental practices; verbal behavior